Суточный ритм питания гусениц совки-ипсилон (Agrotis ypsilon Rоtt.) и восклицательной совки (A. exclamalionis L.) в лабораторных и природных условиях - Ахмедов, Р.М. (Вестник зоологии, 1971)
The caterpillars were studied of the southern (Ordubad 40° N. Lat.) population of A. ypsilon Rott . and A. exclamationis L. and northern (Perm, 59° N. Lat.) population of A. exclamationis L. Under laboratory conditions the experiments were carried out at constant temperature (18°±2°C) and different photoperiods (darkness, 4, 8, 10, 12, 16. 20 and 24 hrs of light a day) and under natural conditions (Old Peterhof of the Leningrad region) The observations were carried out in June 27 and 28 and in August 15 and 18. The results of observations showed that in caterpillars of the both species the rhythm of the diurnal activity is pronounced distinctly. The caterpillars leave the soil and begin feeding when it is getting dark.